Pesticide use in vegetable production in rural Uganda -A case study of Kabale District, South western Uganda - Ngabirano, Hannington; Birungi, Grace (African Journal of Agricultural Research, 2020)
A study to investigate commonly grown vegetables, commonly used pesticides, and pesticide use practices was conducted in Kabale District, in South-western Uganda. This is because indiscriminate pesticide use and poor application practices can leave pesticide residues in food rendering it unsafe for consumption. The study revealed extensive pesticide application in Brassica oleracea; var. capitata (cabbage), Brassica oleracea; var. botrytis (cauliflower), Solanum lycopersicum,(tomato) and Beta vulgaris(beet root). Information obtained using interviews revealed that 16.5%of the Kabale Municipality sold pesticides and 70%of the farmers in the major vegetable growing sub counties of Kaharo, Kyanamira and Kamuganguzi sprayed their vegetables with pesticides. Only 18% of farmers could interpret instructions on pesticide container or bag labels correctly. All farmers (100%) had never attended any training on pesticide use. Cypermethrin, dimethoate, dichlorvos, metalaxyl, profenofos, malathion and mancozeb were mentioned as commonly used pesticides in vegetables grown in the district. Some of the farmers (42%) used mixed different pesticides in the vegetables. Limited knowledge about pesticide application, inability to interpret instructions, non-observance of pre-harvest intervals, mixing pesticides and lack of training on pesticide use contribute to pesticide use malpractices which may put farmers’ health at risk and reduce food quality. Therefore, there is need to address the identified knowledge gaps on safer pesticide application in order to attain safe agricultural productivity for sustainable food security, safeguarding human health and community development in Kabale District, Uganda.
Keywords: Pesticides; vegetables; pesticide use practices; Kabale District; Uganda